The Distribution, Migration Phenology and Spatial and Temporal Status of Hirundinidae Species in Turkey - Esra Per; Kiraz Erci̇yas-yavuz; Nizamettin Yavuz (Trakya University Journal of Natural Sciences, 2016)
In this study, the distributions, migration phenology and spatial and temporal observation status of 5 summer migrant Hirundinidae species (Riparia riparia, Ptyonoprogne rupestris, Hirundo rustica, Cecropis daurica, Delichon urbicum) in Turkey were evaluated. The observation records of the species were compiled from KuşBank database, personal notes and from published materials (thesis, article, book, report, trip reports and web pages). In order to reveal the species distributions during spring and autumn migration periods temporally, distribution maps were prepared using observation data based on 15 days intervals. The 15 days intervaled distributions of R. riparia, H. rustica and D. urbicum revealed that these species showed latitudinal differences. However, the difference was not clear for C. daurica and P. rupestris because of incomplete data and because P. rupestris winters along Mediterranean coasts. R. riparia, H. rustica and D. urbicum distributed along Mediterranean and Aegean coasts in spring until the end of March, spread later first to Central Anatolia and then to northern areas in Turkey and this pattern reversed in autumn period. The latitudinal climatic differences and the resulting food availability are thought to be the reasons for such a distribution difference.